Answer:
B) add 4 times the second equation to 3 times the first equation
Explanation:
So you have these two equations:
2x - 4y = 6
-3x + 3y = 12
In order "to solve this system of equations by elimination" we want to make BOTH of the equations have a term (in this case the y term) and have the same coefficient (that's the number right next to the y) If they are the exactly same number, even the same sign in front, then we would subtract the equations. If they have the same coefficient but different signs, then we would add the equations. This will eliminate the y term completely. So in order to make them have the same coefficient. We'll multiply the first equation by 3 and the second equation by 4
3(2x - 4y = 6)
4(-3x + 3y = 12) multiplying all the way across the equation (distributing)
We'll get
6x -12y = 18
-12x + 12y = 48 Then you are actually adding from the top, down and get one equation from adding the two existing ones together.
-6x = 66 And then you are able to solve it by dividing both sides by -6 to get
x = -11
You can then use either equation and x = -11 to find y. Your solution is the x, y pair. You can check it by putting the x and y into both equations and finding it makes a true statement in both.